Measurement of the time structure of FLASH beams using prompt gamma rays and secondary neutrons as surrogates - Charyyev, Serdar; Liu, Ruirui; Yang, Xiaofeng; Zhou, Jun; Dhabaan, Anees; Dynan, William S; Oancea, Cristina; Lin, Liyong (Physics in medicine and biology, 2023)
Objective. The aim of this study was to investigate the feasibility of online monitoring of irradiation time (IRT) and scan time for FLASH proton radiotherapy using a pixelated semiconductor detector.Approach. Measurements of the time structure of FLASH irradiations were performed using fast, pixelated spectral detectors based on the Timepix3 (TPX3) chips with two architectures: AdvaPIX-TPX3 and Minipix-TPX3. The latter has a fraction of its sensor coated with a material to increase sensitivity to neutrons. With little or no dead time and an ability to resolve events that are closely spaced in time (tens of nanoseconds), both detectors can accurately determine IRTs as long as pulse pile-up is avoided. To avoid pulse pile-up, the detectors were placed well beyond the Bragg peak or at a large scattering angle. Prompt gamma rays and secondary neutrons were registered in the detectors' sensors and IRTs were calculated based on timestamps of the first charge carriers (beam-on) and the last charge carriers (beam-off). In addition, scan times inx,y, and diagonal directions were measured. The experiment was carried out for various setups: (i) a single spot, (ii) a small animal field, (iii) a patient field, and (iv) an experiment using an anthropomorphic phantom to demonstratein vivoonline monitoring of IRT. All measurements were compared to vendor log files.Main results. Differences between measurements and log files for a single spot, a small animal field, and a patient field were within 1%, 0.3% and 1%, respectively.In vivomonitoring of IRTs (95-270 ms) was accurate within 0.1% for AdvaPIX-TPX3 and within 6.1% for Minipix-TPX3. The scan times inx,y, and diagonal directions were 4.0, 3.4, and 4.0 ms, respectively.Significance. Overall, the AdvaPIX-TPX3 can measure FLASH IRTs within 1% accuracy, indicating that prompt gamma rays are a good surrogate for primary protons. The Minipix-TPX3 showed a somewhat higher discrepancy, likely due to the late arrival of thermal neutrons to the detector sensor and lower readout speed. The scan times (3.4 ± 0.05 ms) in the 60 mm distance ofy-direction were slightly less than (4.0 ± 0.06 ms) in the 24 mm distance ofx-direction, confirming the much faster scanning speed of the Y magnets than that of X. Diagonal scan speed was limited by the slower X magnets.
Keywords: protonová terapie; záření gama; Protons; radiometrie; Gamma Rays; FLASH; protony; Neutrons; proton therapy; secondary neutrons; Radiometry; prompt gamma; neutrony; semiconductor detector; dose rate; Proton Therapy